Biosensors : kinetics of binding and dissociation using fractals - Sadana, Ajit, 1947- (Elsevier, 2003)
This title brings to the attention of researchers in the industry, and in academia, the application of fractals to help in modeling the analyte/receptor binding and dissociation kinetics on biosensor surfaces. The work builds on that done in Engineering Biosensors: Kinetics and Design Applications, published by Academic Press in 2002. In particular, more examples are provided of where biosensors may be effectively used. This sequel is extremely timely, given the anticipation that the applications and reliance on biosensors will increase due to the advances in miniaturization, (wireless) communications, and the development of new materials (especially biological and chemical). Other applications of biosensors on the increase can be found in: the protection of civilian structures and infrastructures; protection from possible biological and chemical threats; health care; energy; food safety; and the environment to name a few. - Covers all areas of applications of biosensors - No other book on biosensors describes the kinetics of binding - Provides numerous examples of where biosensors may be used.